Lymphomatoid papulosis in a patient treated with glatiramer acetate and the glatiramoid Glatopa for multiple sclerosis: A case report. (19th November 2021) - Shirani, Afsaneh; Dalton, Scott R; Avery, Eric J; Arcot Jayagopal, Lakshman; Meyer, Christina; Stuve, Olaf; Zabad, Rana
A 48-year-old Caucasian woman with history of multiple sclerosis (MS) presented with erythematous papulonodular lesions in her extremities and trunk. She was being treated with glatiramer acetate (GA) for the past 10 years and the glatiramoid, Glatopa, for 2 years prior to this presentation. A skin biopsy showed CD30 + lymphoproliferative disorder consistent with lymphomatoid papulosis (LyP). Three weeks after stopping Glatopa, her skin lesions were improved. It remains unclear whether GA's or Glatopa's capability to alter T-cell differentiation, may have a link with LyP. This case report is a reminder to be vigilant for skin lesions in patients with MS.